Gender and Agricultural Risk : A Gendered Approach to Agricultural Risk Assessments and Management Strategies - World Bank (World Bank, Washington, DC, 2017)
The objective of this paper is to develop an approach for integrating a gender dimension into Agricultural Sector Risk Assessments (ASRAs). The focus is on the approach because both agricultural risk and gender issues are contextual, thus the outcomes of a gender-based risk assessment are highly dependent on the social, cultural, geo-graphic, and economic contexts of the setting in which the assessment is applied. The organization of the paper reflects the challenges of incorporating a gender dimension into ASRAs. The conceptual framework and step-by-step illustrations presented herein are based on lessons learned by the World Bank and other institutions in assisting developing economies in conducting sector and key commodity supply chain risk assessments (World Bank 2015a). The paper also relies on recent work by international institutions and academic research that offer insights into the complexities of gender issues in relation to agricultural shocks. These experiences inform this paper’s case for a gender-based approach to Agriculture Risk Management (ARM) and help to illustrate a practical, stepwise approach for conducting gender-based ASRAs. This paper is arranged as follows: Chapter 2 offers a summary of the conceptual framework for risk management, including addressing why a gendered approach to ASRAs is essential; Chapter 3 shows the available evidence that agricultural risk has a gender-differentiated impact on farming households and that farming households adopt a gender-differentiated response to risk; Chapter 4 describes a step-by-step operational approach for doing so, and includes guidance for formulating gender-smart policies and strategies for strengthening agricultural systems’ resilience; and Chapter 5 presents a summary of findings and concluding remarks.